2021
DOI: 10.1021/acs.analchem.1c02662
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Carbonaceous Counterfeits in Graphene Materials Using the Thermogravimetric Analysis (TGA) Approach

Abstract: Counterfeits in the supply chain of high-value advanced materials such as graphene and their derivatives have become a concerning problem with a potential negative impact on this growing and emerging industry. Recent studies have revealed alarming facts that a large percentage of manufactured graphene materials on market are not graphene, raising considerable concerns for the end users. The common and recommended methods for the characterization of graphene materials, such as transmission electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The aim of assessing this parameter was to confirm the consistency of the TGA method to determine the thermal stability of GR2Ms, which is an important physical parameter defining their properties. 22,23 Results reported by participants (PP) and their LP analysis for all GR2Ms samples are summarized in Figures S6, S7 and Tables S3, S4. The results showed that 10 participants reported the thermal stability of GO in the expected range of 100−150 °C, while two participants (3 and 7) showed higher thermal stability between 180−250 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of assessing this parameter was to confirm the consistency of the TGA method to determine the thermal stability of GR2Ms, which is an important physical parameter defining their properties. 22,23 Results reported by participants (PP) and their LP analysis for all GR2Ms samples are summarized in Figures S6, S7 and Tables S3, S4. The results showed that 10 participants reported the thermal stability of GO in the expected range of 100−150 °C, while two participants (3 and 7) showed higher thermal stability between 180−250 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These “bulk” or average properties of manufactured GR2Ms produced at large batches (e.g., 10–100 kg) are equally important for manufacturers and the end-users. Methods such as light microscopy (number of layers), gas adsorption analysis by the Brunauer–Emmett–Teller method (specific surface area), pH titration (acids and oxygen groups), TGA (qualitative and quantitative determination of components, thermal properties), and laser diffraction or dynamic light scattering (particle size distribution, PSD) have been successfully used and recommended for simple and low-cost characterizations of GR2Ms. Some of these methods are currently under evaluation to assess their characterization capability, uncertainties, and limitations needed to developing reliable ISO standards.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In a commercially available TGA instrument, a thermobalance with a submicrogram (sub-μg) mass resolution is used to measure material mass loss during a programmed heating procedure. Sample consumption of the mg level is usually needed to obtain a resulting TGA curve that contains quantitative information related to a temperature-dependent mass change, thereby analyzing the material structure, 5 composition, 6 thermal stability, 7 and reaction kinetics. 8 For a sample under TGA, the decomposition of the material may change the molecular formula or material phase of the sample, which is often accompanied by morphology change in the nanostructure.…”
Section: ■ Introductionmentioning
confidence: 99%